Comparative Study of Divorce in Islamic Family Law and Buddhist Ethics - Fery Suryono (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research undertakes a comparative analysis of the concept of divorce within the frameworks of Islamic Family Law and Buddhist Ethics. Marriage, recognized as a profound bond of both physical and spiritual union, holds significant value in both religious traditions. However, contemporary social realities reveal a high incidence of divorce, prompting a critical examination of the legal and ethical mechanisms governing its dissolution. Within Islamic jurisprudence, divorce (talak) is permitted but considered detestable by Allah, governed by stringent procedural mechanisms including talak (the husband’s right), khulu’ or gugat cerai (the wife’s right to initiate), and fasakh (judicial intervention). These processes carry clear legal implications concerning the waiting period (iddah), the possibility of reconciliation (rujuk), and the division of marital property. Conversely, while Buddhism does not explicitly prohibit divorce, the teachings of the Buddha strongly encourage spouses to exhaust all avenues for peaceful conflict resolution before considering separation as a last resort. The ethical framework in Buddhism grants equal rights to both parties to dissolve the marriage. This study employs a qualitative descriptive analytical method through library research, drawing upon primary legal texts such as Indonesia’s Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI) for Muslims, alongside the Vinaya Pitaka for adherents of Buddhism. The findings indicate that while both traditions view divorce as a final option, they diverge fundamentally in their legal structures; Islamic law establishes specific, gender-differentiated rights and obligations, whereas Buddhist ethics emphasize mutual consent and personal responsibility without formal legalistic procedures. The research concludes by recommending that couples, regardless of faith, prioritize reconciliation and peace, aligning with the core principles of both religions, and urges policymakers and legal practitioners to promote harmonious family life and reconsider legal frameworks that might better serve the welfare of children and families.